THE RENAISSANCE FRENCH PSALTER. (THE ROMANIAN VERSIFICATION OF THE PSALMS WITH HUGUENOT MELODIES. ON THE OCCASION OF CELEBRATING THE 450th ANNIVERSARY OF THE FIRST FRENCH PSALTER, 1562-2012), Academy Publishing House, Bucharest, 2012 (435 pages, ISBN 978-973-27-2277-0) - Anamaria Mădălina HOTORAN (Studia Universitatis Babeş-Bolyai. Musica)
The Renaissance French Psalter published by the Romanian Academy, addresses the ecclesiastic community as well as the academic one, by restoring a Christian heritage of great cultural and spiritual value.